Prosthetic Valve Endocarditis Caused by Bartonella henselae: A Case Report of Molecular Diagnostics Informing Nonsurgical Management. (9th November 2016) - Bartley, Patricia; Angelakis, Emmanouil; Raoult, Didier; Sampath, Rangarajan; Bonomo, Robert A.; Jump, Robin L. P.
Abstract: Identifying the pathogen responsible for culture-negative valve endocarditis often depends on molecular studies performed on surgical specimens. A patient with Ehlers-Danlos syndrome who had an aortic graft, a mechanical aortic valve, and a mitral anulloplasty ring presented with culture-negative prosthetic valve endocarditis and aortic graft infection. Research-based polymerase chain reaction (PCR)/electrospray ionization mass spectrometry on peripheral blood samples identified Bartonella henselae . Quantitative PCR targeting the16S-23S ribonucleic acid intergenic region and Western immunoblotting confirmed this result. This, in turn, permitted early initiation of pathogen-directed therapy and subsequent successful medical management of B henselae prosthetic valve endocarditis and aortic graft infection.